Business strategies and advanced techniques for entrepreneurship 4.0 - Sáiz Álvarez, José Manuel (Business Science Reference, 2018)
"This book explores what business strategies can be developed by organizations to have a process of sustainable growth over time, that is, preserving the environment for the next generations and currently caring for the human resources of the organization"- Resumé vydavatel
Keywords: management; podnikatelské projekty; inovace; business planning; innovations; monografie; elektronické knihy; monographs; electronic books